Az erdélyi gyerekirodalom története a rendszerváltástól napjainkig - Makkai, Kinga (Studia Litteraria, 2019)
The study examines the changes in Transylvanian children’s literature from the regime change up until today. In the past nearly thirty years the two separate literary periods were differentiated by the so called “new middle generation”, the literary period that emerged in the end of the first decade of the 21st century and which period saw the “the boom of children’s literature”. Although the continuous presence of the outstanding representatives - who started their work before the regime change - in the Transylvanian children’s literary common knowledge significantly join the two periods, yet those new plot, formal and linguistic characteristics that contributed to the renewal of children’s literature in the past two decades are demonstrable.